The forgotten children of Africa: Voicing HIV and Aids orphans" stories of bereavement: a narrative approach - Richter, Amanda (HTS teologiese studies, 2005)
This article looks at the bereavement of children left orphaned by the HIV and Aids pandemic that is crippling the continent of Africa. Their bereavement is examined by means of the narrative approach and by integrating this approach with the traditional African art of storytelling. By listening to the stories of three Zulu children, the article gives them the opportunity to express their own unique stories of bereavement: stories that would otherwise have been silenced by the wave of bereavement in the wake of countless deaths worldwide as a result of HIV and Aids infection. It looks at the losses these children have suffered, their greatest fears and how their Zulu culture and customs influence their emotional experience of losing their parents. The article shows how they can – by means of storytelling – reformulate the story of their lives and find the proverbial pot of gold at the end of the rainbow.